Measuring Economic Contribution and Per Capita Income Disparities in Indonesia Using the Theil Index - Zul Ammar; Nasri Bachtiar (Transpublika Publisher, 2024)
This study aims to analyze economic contribution and per capita income disparities among provinces in Indonesia using the Theil Index method. The results indicate that the total economic contribution disparity among provinces has a value of 2.2716, with the intra-island disparity (Tintra) component accounting for 1.4919 and the inter-island disparity (Tinter) component accounting for 1.2237. Meanwhile, the analysis of per capita income disparity shows a Total Theil Index of 0.8520, with the Tintra component accounting for 0.8384 and the Tinter component accounting for 0.0136. These findings highlight that intra-island disparities play a more dominant role than inter-island disparities. Therefore, policies focused on equitable infrastructure development in remote areas and the acceleration of development in eastern Indonesia are essential to reduce these disparities. This study also recommends that further research should be conducted to explore the factors contributing to these disparities.